2022
DOI: 10.7759/cureus.29317
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Interventions for the Management of Obesity: A Literature Review

Abstract: The gut microbiota (GM) has been recognized as an important factor in the development of metabolic diseases such as obesity; it has been reported that the composition of the GM differs in obese and lean subjects, suggesting that microbiota dysbiosis can contribute to changes in body weight. Dysbiosis occurs due to an imbalance in the composition of gut bacteria, changes in the metabolic process, or changes in the distribution of microbiota within the gut. Dysbiosis can change the functioning of the intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…While an obesogenic WD plays a critical role in remodeling the gut microbiome, foods rich in prebiotics may stimulate the intestinal growth of Lactobacillus and Bifidobacterium and reduce bacteria belonging to the phyla Firmicutes and Bacteroidetes that can prevent or even treat overweight and obesity [8,32]. SDexF is a short-chain glucose polymer obtained by the modification of potato starch [20].…”
Section: Discussionmentioning
confidence: 99%
“…While an obesogenic WD plays a critical role in remodeling the gut microbiome, foods rich in prebiotics may stimulate the intestinal growth of Lactobacillus and Bifidobacterium and reduce bacteria belonging to the phyla Firmicutes and Bacteroidetes that can prevent or even treat overweight and obesity [8,32]. SDexF is a short-chain glucose polymer obtained by the modification of potato starch [20].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the majority of our identified metabolites are gut microbiota–related metabolites. Indeed, obesity is closely related to the gut microbiota [28], and studies have shown that an imbalance in the gut microbiome is a significant factor that contributes to obesity and the development of metabolic diseases [29]; moreover, microbiota management has emerged as a novel approach to treating obesity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, obesity is closely related to T A B L E 3 Significant pathways associated with obesity in male and female groups using different measurements of obesity. the gut microbiota [28], and studies have shown that an imbalance in the gut microbiome is a significant factor that contributes to obesity and the development of metabolic diseases [29]; moreover, microbiota management has emerged as a novel approach to treating obesity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics, probiotics, synbiotics, FMT, and other therapies can be used[ 17 ]. These therapies depend on the structure and composition of the resident microbiota and a thorough understanding of the dynamic changes that occur over time[ 109 , 110 ]. Through intensive research, some processes of the gut microbiota have been better studied in relation to their association with obesogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%